2015
DOI: 10.1136/neurintsurg-2015-011998
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic variation and potential impact of anesthetics used during endovascular management of acute ischemic stroke

Abstract: Background Multiple authors have reported that “general anesthesia”(GA), as a generic and uncharacterized therapy, is contraindicated for patients undergoing endovascular management of acute ischemic stroke(EMAIS). The recent AHA update cautiously suggests that it might be reasonable to favor conscious sedation over GA during EMAIS. We are concerned that such recommendations will result in patients undergoing endovascular treatment without consideration of the effects of specific anesthetic agents, anesthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 26 publications
3
49
0
2
Order By: Relevance
“…Previous studies examined the occurrence of such single extreme blood pressure values. One did find significant associations with outcome,17 while others could not 18 19. Another study investigating both patients under conscious sedation and GA found lower minimum diastolic blood pressures in patients with worse outcome 20.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies examined the occurrence of such single extreme blood pressure values. One did find significant associations with outcome,17 while others could not 18 19. Another study investigating both patients under conscious sedation and GA found lower minimum diastolic blood pressures in patients with worse outcome 20.…”
Section: Discussionmentioning
confidence: 93%
“…[12][13][14][15][18][19][20][21][22][23] Interestingly, a recent study suggested that volatile anaesthetics were associated with a better outcome in patients subjected to EVT interventions for AIS. The retrospective studies have only reported GA as a generic and uncharacterized therapy.…”
Section: Discussionmentioning
confidence: 99%
“…18 Thirdly, the preferred method of anaesthesia for EVT may have changed, now favouring the use of CS. This finding may partly be explained by the substantial number of past retrospective studies suggesting worse neurological outcome and even increased mortality in patients subjected to EVT in GA. [12][13][14][15][20][21][22][23][24] However, most of these studies were biased because as GA was often selected for patients with more severe illness, thus prone to worse outcome. The extent to which the degree of stroke deficit influenced the decision of CS vs. GA among Nordic anaesthetic departments was not answered by this questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 This is significant because temporary vessel clipping during these surgeries may increase cerebral-ischaemia risk, yet no appreciable neurological deterioration was noted at 24 h [OR 1.155 (95% CI 0.777e1.717); P¼0.475] or 3 months [OR 0.981 (95% CI 0.625e1.368); P¼0.926] with supplemental anaesthetic administration. Nonetheless, anaesthetic variation during endovascular stroke rescue may impact outcomes, 27 and intraoperative burst suppression might be an independent risk factor for postoperative delirium. 28 Final results from the GOLIATH trial may allow for additional evaluation of neurological injury and outcomes in relation to anaesthetic dosing.…”
Section: New Scientific Model For Anaesthetic Neurotoxicity?mentioning
confidence: 99%